The Influence of Current Ratio, Debt to Equity Ratio, and Dividend Yield on Stock Returns in the Food and Beverage Sub-sector Before and During COVID-19 - Fatikha Hamaya Maharani; Ali Riza Fahlevi (Academic Bright Collaboration, 2026)
Purpose - Using data collected both before and during the COVID-19 epidemic, this research compares the stock returns of food and beverage subsector businesses listed on the Indonesia Stock Exchange before and after implementing changes to the current ratio (CR), debt-to-equity ratio (DER), and dividend yield (DY). The objective is to learn the impact of financial parameters on stock performance and investor choices in both normal and crisis market scenarios. Methods – A quantitative approach with panel data regression was employed, using secondary data from annual reports and stock market databases for 2017–2022. The analysis included descriptive statistics, citu wolassical assumption tests, t-tests for partial effects, and F-tests for simultaneous effects. Findings – The results demonstrate that there is a positive and statistically significant relationship between the disclosure of current ratio, debt to equity ratio, and dividend yield in the pre- and post-pandemic periods and stock returns (F-statistic = 0.0006). Before the pandemic, CR had a positive and statistically significant impact (p = 0.0000), while during the epidemic, the Debt to Equity Ratio had a positive and statistically significant effect (p = 0.0000). A value of 0.217785 for the pre-pandemic era and 0.199099 for the post-pandemic period is represented by the adjusted coefficient of determination (adjusted R-square). Research implications – These findings provide practical insights for corporate financial strategy and investor decision-making, highlighting the importance of considering both financial ratios and broader macroeconomic conditions. The study also contributes empirical evidence on stock return determinants under crisis conditions, enhancing understanding of the interplay between liquidity, leverage, and dividend policies. This study only compares test results in the periods before and during the COVID-19 pandemic descriptively through two separate regression models. This study has not included variables that specifically represent pandemic conditions, so the differences in results between periods cannot yet directly reflect the impact of the pandemic. Originality – This study examines the effect of the Current Ratio, Debt to Equity Ratio, and Dividend Yield on the stock returns of the food and beverage sub-sector on the IDX before and during the pandemic, using separate regression models for each period. The findings indicate significant differences between the pre-pandemic and pandemic periods, while also providing guidance for sector-specific research in emerging markets. This analysis is based on the signaling theory framework, which assumes that financial ratios and dividends provide important information to investors about a company's prospects.